2000
DOI: 10.1074/jbc.275.11.7443
|View full text |Cite
|
Sign up to set email alerts
|

Differential Targeting of Shaker-like Potassium Channels to Lipid Rafts

Abstract: Ion channel targeting within neuronal and muscle membranes is an important determinant of electrical excitability. Recent evidence suggests that there exists within the membrane specialized microdomains commonly referred to as lipid rafts. These domains are enriched in cholesterol and sphingolipids and concentrate a number of signal transduction proteins such as nitricoxide synthase, ligand-gated receptors, and multiple protein kinases. Here, we demonstrate that the voltagegated K ؉ channel Kv2.1, but not Kv4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
214
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(232 citation statements)
references
References 35 publications
16
214
2
Order By: Relevance
“…Details with respect to these methods are contained within SI Text and corresponding references (13,14,26,(32)(33)(34)(35)(36). Only low passage number (<45) HEK cells lacking endogenous K + channel activity were used.…”
Section: Methodsmentioning
confidence: 99%
“…Details with respect to these methods are contained within SI Text and corresponding references (13,14,26,(32)(33)(34)(35)(36). Only low passage number (<45) HEK cells lacking endogenous K + channel activity were used.…”
Section: Methodsmentioning
confidence: 99%
“…4A). Because the stability of the interaction of hSlo-N200A with lipid rafts to detergent extraction might be low, we also have used an alternative detergent-free method for lipid raft isolation based on sodium carbonate extraction at pH 11 (38). This procedure showed more hSlo-N200A floating in low buoyancy fractions (Fig.…”
Section: Overexpressed Hslo Is Efficiently Transported To the Cell Sumentioning
confidence: 99%
“…Procedures to obtain permanent transformants; assess protein expression by metabolic labeling; determine polarity by domainspecific biotinylation in cells cultured on Transwell chambers, or by indirect immunofluorescence; and measure relative density of fluorograms all have been described (36,37). Lipid raft association was assessed by isolating low density membrane fractions after either ice-cold detergent extraction or sodium carbonate extraction (100 mM or 500 mM) pH 11 at 4°C for 20 min, as described (38), except that in both cases, floatation of lipid rafts was made on linear sucrose gradients without eliminating cell debris.…”
Section: Transfection and Assessment Of Protein Expression Polaritymentioning
confidence: 99%
“…Several recent studies (17,18) have indicated that voltagegated potassium channels segregate into specialized membrane microdomains modulating their activity. The predominant voltage-gated potassium channel of T lymphocytes is Kv1.3.…”
mentioning
confidence: 99%